How leaders restrict employees’ deviance: An integrative framework of interactional justice and ethical leadership - Li, Jinsong; Wang, Haoding; Cai, Yahua; Chen, Zhijun (Frontiers in Psychology, 2022)
Past research illustrated that leaders could restrict followers’ deviance by reinforcing social norms of appropriate behaviors. Nevertheless, we submit that this understanding is incomplete without considering the effects of leaders on followers’ self-sanctions given that most undesirable behaviors are controlled internally. This research argues that interactional justice is an effective strategy for leaders to enhance followers’ self-sanctions. Leaders’ interactional justice provides personalized information and dyadic treatment that indirectly reduce employees’ deviance by restraining followers’ moral disengagement. Besides, this study examines the social sanction role of ethical leadership. Ethical leaders highlight the importance of adherence to collective norms, which influence the relationship between followers’ moral disengagement and deviance. By identifying the different pathways via which they influence followers’ moral disengagement, we integrate interactional justice and ethical leadership in one theoretical framework. Our predictions are supported by data analyses of 220 samples from a multi-wave and -source field study. This integrative framework contributes to a comprehensive understanding of how leaders restrict employees’ deviance.